Effects of variable resistance training within complex training on strength and punch performance in elite amateur boxers - Liu, Y.; Huang, Z.; Zhou, Z.; Zhang, L.; Guo, Y.; Chen, C. (Frontiers in Physiology, 2024)
Objectives: This study explored the effects of 6 weeks of variable resistance training (VRT) and constant resistance training (CRT) within complex training, on muscle strength and punch performance.